A trimeric coiled-coil motif binds bacterial lipopolysaccharides with picomolar affinity - Hatlem, Daniel; Christensen, Mikkel; Broeker, Nina K.; Kristiansen, Per E.; Lund, Reidar; Barbirz, Stefanie; Linke, Dirk (Frontiers in Cellular and Infection Microbiology, 2023)
α-helical coiled-coils are ubiquitous protein structures in all living organisms. For decades, modified coiled-coils sequences have been used in biotechnology, vaccine development, and biochemical research to induce protein oligomerization, and form self-assembled protein scaffolds. A prominent model for the versatility of coiled-coil sequences is a peptide derived from the yeast transcription factor, GCN4. In this work, we show that its trimeric variant, GCN4-pII, binds bacterial lipopolysaccharides (LPS) from different bacterial species with picomolar affinity. LPS molecules are highly immunogenic, toxic glycolipids that comprise the outer leaflet of the outer membrane of Gram-negative bacteria. Using scattering techniques and electron microscopy, we show how GCN4-pII breaks down LPS micelles in solution. Our findings suggest that the GCN4-pII peptide and derivatives thereof could be used for novel LPS detection and removal solutions with high relevance to the production and quality control of biopharmaceuticals and other biomedical products, where even minuscule amounts of residual LPS can be lethal.